PENGARUH JUMLAH SIMPANAN TERHADAP SISA HASIL USAHA (SHU) KOPERASI DI KABUPATEN KAMPAR - Safas, Rahmat; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Objective: The purpose of this study to determine the effect of the amount of savings to the rest of the business results in the cooperative in Kampar.  Methods: The population is all cooperative in Kampar. Sampling technique that will be used is purposive sampling technique and obtained sample of six cooperatives.This study uses secondary data from Annual Members Meeting (RAT) data in 2013 until 2018. Methods of collecting data are observation and documentation methods. Data analysis techniques used include 1) Classic Assumption Test which includes Normality Test, Heteroscedasticity Test, Multicollinearity Test and Autocorrelation Test 2) Testing the hypothesis using simple linear regression method. Results: The results of the hypothesis test tcount  were 3.686 and the significance level was 0.001 and the results of the ttable were 2.03224. From these data it can be seen from the tcount greater than ttable (3.686> 2.03224) and a significant value of 0.001 <0.05. Conclusion:  There is an effect of the amount of savings to the rest of the business results in the cooperative in Kampar.  Key: Total savings, net income on cooperative operations, cooperative